Early preterm delivery due to placenta previa is an independent risk factor for a subsequent spontaneous preterm birth - Erez Offer; Novack Lena; Klaitman Vered; Erez-Weiss Idit; Beer-Weisel Ruthy; Dukler Doron; Mazor Moshe (BMC Pregnancy and Childbirth, 2012)
Abstract Background To determine whether patients with placenta previa who delivered preterm have an increased risk for recurrent spontaneous preterm birth. Methods This retrospective population based cohort study included patients who delivered after a primary cesarean section (n = 9983). The rate of placenta previa, its recurrence, and the risk for recurrent preterm birth were determined. Results Patients who had a placenta previa at the primary CS pregnancy had an increased risk for its recurrence [crude OR of 2.65 (95% CI 1.3-5.5)]. The rate of preterm birth in patients with placenta previa in the primary CS pregnancy was 55.9%; and these patients had a higher rate of recurrent preterm delivery than the rest of the study population (p < .001). Among patients with placenta previa in the primary CS pregnancy, those who delivered preterm had a higher rate of recurrent spontaneous preterm birth regardless of the location of their placenta in the subsequent delivery [OR 3.09 (95% CI 2.1-4.6)]. In comparison to all patients with who had a primary cesarean section, patients who had placenta previa and delivered preterm had an independent increased risk for recurrent preterm birth [OR of 3.6 (95% CI 1.5-8.5)]. Conclusions Women with placenta previa, who deliver preterm, especially before 34 weeks of gestation, are at increased risk for recurrent spontaneous preterm birth regardless to the site of placental implantation in the subsequent pregnancy. Thus, strict follow up by high risk pregnancies specialist is recommended.